Strengthening Community-Based Drug Abuse Prevention: A Collaborative P4GN Program Between University Students and the National Narcotics Board in Rural Indonesia: Penguatan Pencegahan Penyalahgunaan Narkoba Berbasis Komunitas: Kolaborasi Program P4GN Mahasiswa Perguruan Tinggi dan Badan Narkotika Nasional di Wilayah Pedesaan Indonesia - Dini Fauziyah Fathulaila; Dini Sheila Muflikhah; Dwi Lomansari; Miftahul Iman; Achmad Faisal Ramadhani; Avicenna Muda Khulafi Zen; Mohammad Muhyidin (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2026)
Drug abuse is a social problem that has expanded beyond urban areas and increasingly affects rural communities. Limited public knowledge regarding the types, impacts, and prevention strategies of drug abuse contributes to community vulnerability toward illicit substance use. This community service program aimed to improve public awareness and understanding of drug abuse prevention in Kambingan Village, Pagu District, Kediri Regency, through the Prevention, Eradication, Abuse, and Illicit Drug Trafficking Program (Pencegahan, Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkoba – P4GN). The program was implemented using a Participatory Action Research (PAR) approach involving collaboration among students of the KKN program at UIN Syekh Wasil Kediri, the National Narcotics Board (BNN), village authorities, and local communities. The activities included problem identification, interactive educational sessions, discussions, question-and-answer sessions, and evaluation through observation, interviews, and documentation. The results indicated an improvement in community understanding regarding drug types, negative impacts, distribution patterns, and preventive actions at the family and community levels. Furthermore, the program encouraged community participation through initiatives for environmental monitoring and continuous drug prevention education. A community-based P4GN program through a participatory approach represents a potential strategy for strengthening collective awareness and social resilience against drug abuse threats.